Beaver dams attenuate flow: A multi‐site study. Issue 2 (1st January 2021) - Puttock, Alan; Graham, Hugh A.; Ashe, Josie; Luscombe, David J.; Brazier, Richard E.
Abstract: Beavers can profoundly alter riparian environments, most conspicuously by creating dams and wetlands. Eurasian beaver ( Castor fiber ) populations are increasing and it has been suggested they could play a role in the provision of multiple ecosystem services, including natural flood management. Research at different scales, in contrasting ecosystems is required to establish to what extent beavers can impact on flood regimes. Therefore, this study determines whether flow regimes and flow responses to storm events were altered following the building of beaver dams and whether a flow attenuation effect could be significantly attributed to beaver activity. Four sites were monitored where beavers have been reintroduced in England. Continuous monitoring of hydrology, before and after beaver impacts, was undertaken on streams where beavers built sequences of dams. Stream orders ranged from 2nd to 4th, in both agricultural and forest‐dominated catchments. Analysis of >1000 storm events, across four sites showed an overall trend of reduced total stormflow, increased peak rainfall to peak flow lag times and reduced peak flows, all suggesting flow attenuation, following beaver impacts. Additionally, reduced high flow to low flow ratios indicated that flow regimes were overall becoming less "flashy" following beaver reintroduction. Statistical analysis, showed the effect of beaver to be statistically significant in reducing peak flows with estimated overall reductions in peak flows from −0.359 to −0.065 m 3 s −1 across sites. Analysis showed spatial and temporal variability in the hydrological response to beaver between sites, depending on the level of impact and seasonality. Critically, the effect of beavers in reducing peak flows persists for the largest storms monitored, showing that even in wet conditions, beaver dams can attenuate average flood flows by up to ca. 60%. This research indicates that beavers could play a role in delivering natural flood management. Abstract : Four sites were monitored where beavers have been reintroduced in Great Britain to understand the impacts of beaver dams upon flow attenuation. Analysis of >1000 storm events showed an overall trend of reduced total stormflow, increased peak rainfall to peak flow lag times and reduced peak flows. Analysis showed flow attenuation impacts due to beaver damming to persist during largest flood events, whilst additionally flow regimes became overall less flashy following beaver impact.